Adverse Effects of Surgically Accelerated Orthodontic Techniques: A Systematic Review - Ioanna Pouliezou; Angeliki Xenou; Konstantina Vavetsi; Anastasia Mitsea; Iosif Sifakakis (MDPI AG, 2022)
Evidence on the potential adverse effects of surgically accelerated orthodontic techniques is scarce. The aim of this review was to evaluate the available scientific evidence regarding the adverse effects on periodontium, tooth vitality, and root resorption, associated with these surgical procedures in children, adolescents, and adults. The reporting of this review was based on the PRISMA2020 guidelines. Seven databases and three registers were searched for randomized clinical trials (RCTs) and controlled clinical trials (CCTs) published up to 22 June 2022. Hand searching of the reference lists of the included studies was also performed. The quality of the evidence was assessed with the Cochrane risk of bias and ROBINS-I tools. A total of 887 records were initially screened. Finally, 33 RCTs (713 patients), six CCTs (103 patients), and six ongoing protocols were eligible for this systematic review. The current review indicated that there are no significant adverse effects of surgically accelerated orthodontic techniques on periodontium, root length, or tooth vitality. High-quality clinical trials with less risk of bias should be conducted to allow reliable conclusions regarding the adverse effects of the surgical procedures associated with the acceleration of orthodontic treatment on children, adolescents, and adults.